2004
DOI: 10.1111/j.1399-3089.2004.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Are N‐glycolylneuraminic acid (Hanganutziu–Deicher) antigens important in pig‐to‐human xenotransplantation?

Abstract: Carbohydrate structures on PRBC are different from those on PAEC. Healthy human sera contain anti-nonGal IgG antibodies to NeuGc expressed on PRBC, but not on PAEC. We speculate that anti-nonGal IgG antibodies to PRBC can recognize both NeuGc and protein, and this may be the reason why such antibodies have not been detected by ELISA. A definite conclusion about the immunogenicity of NeuGc has not been obtained. More sera from patients (not from non-human primates) sensitized with porcine cells or organs need t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 31 publications
(46 reference statements)
1
88
0
Order By: Relevance
“…Moreover, most humans have circulating anti-Neu5Gc antibodies [9,11] targeting this xenoglycan in serum [9,12]. Levels of anti-Neu5Gc antibodies vary among different individuals, but it has been suggested that chronic exposure to Neu5Gc and incorporation of this xenoglycan combined with circulating anti-Neu5Gc antibodies can promote chronic inflammatory states contributing to various diseases [14] including some of the diseases associated Hanganutziu-Deicher antibodies, which are reactive against Neu5Gc [13,14]. There is also experimental evidence for Neu5Gc acting as a xeno-auto antigen capable of exacerbating an inflammatory reaction within vasculature endothelium [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most humans have circulating anti-Neu5Gc antibodies [9,11] targeting this xenoglycan in serum [9,12]. Levels of anti-Neu5Gc antibodies vary among different individuals, but it has been suggested that chronic exposure to Neu5Gc and incorporation of this xenoglycan combined with circulating anti-Neu5Gc antibodies can promote chronic inflammatory states contributing to various diseases [14] including some of the diseases associated Hanganutziu-Deicher antibodies, which are reactive against Neu5Gc [13,14]. There is also experimental evidence for Neu5Gc acting as a xeno-auto antigen capable of exacerbating an inflammatory reaction within vasculature endothelium [15].…”
Section: Introductionmentioning
confidence: 99%
“…18) On the other hand, other mammals have CMP-NeuAc hydroxylase and NeuGc exist on glycoproteins and glycolipids of the tissues. [14][15][16][17] Then tolerization against NeuGc seems to be established in mice. Actually, even 5.0 g/kg of hot water extracts of P. porrigens collected in 2004 failed to show the toxicity against normal mice on oral administration and finally higher concentrations of extracts (750 and 1000 mg/kg) shown the toxicity against normal mice by intraperitoneal administration.…”
Section: Resultsmentioning
confidence: 99%
“…Humans can not biosynthesize NeuGc because of the loss of cytidine monophospho-NeuAc hydroxylase (CMPNeuAc hydroxylase). [14][15][16][17] Nevertheless humans daily uptake NeuGc in meat (beef, pork, chicken, mutton and so on) and have the antibody production against NeuGc. 18) On the other hand, other mammals have CMP-NeuAc hydroxylase and NeuGc exist on glycoproteins and glycolipids of the tissues.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies demonstrated the production of natural Abs to N-glycolylneuraminic acid in humans and the presence this epitope on pig cells (Zhu & Hurst, 2002;Miwa et al, 2004;Taylor et al, 2010). However, analysis of sera from monkeys sensitized to 1,3GT KO pig tissue demonstrated no significant elevation in the activity of such Abs (Yeh et al, 2010).…”
Section: Anti-non Gal Ab Response In Recipients Of Pig Ligamentmentioning
confidence: 99%